Method of Creating Generation Z’s Preferences in Choosing Streetwear Brands - Theodore, Senon (VCD, 2022)
The main fashion trend, namely streetwear, which is developing in various parts of the world, including Indonesia, is attracting a lot of attention, especially for generation Z. In local streetwear, there are problems found and cited through the Innovation Development Design worksheet (2022), namely: not being a creator so that fake products are mushrooming, interest in young people who buy outdoor streetwear products make the dollar rise, lack of concept development. The solution, through a case study of the preferences of generation Z, can be used as an idea in building the right preferences for targets and developing a Unique Selling Proposition (USP) for streetwear brands in the future. This study is intended to determine the preferences of generation Z to support streetwear brands in the idea development process. To get the maximum study results, in this study a descriptive method with a qualitative and quantitative approach was used. The results of these findings state three preferences from generation Z when choosing streetwear clothing, namely: streetwear clothing preferences based on quality and originality, streetwear clothing preferences based on experience in choosing, and using the latest streetwear clothing preferences on counterfeit products. Through all these preferences, in order to achieve the preferences of generation Z on making new streetwear, it is through design, namely the creation of concepts in designs and messages conveyed because they are teenagers. The output of this journal is expected to be an inspiration for new streetwear brands to create original and growing clothing concept designs. Keywords: Streetwear, Preference, Design, Concept